Isolation and Intensive Care (ICU) Service, Surge Capacity and Pandemic Training in Government Designated COVID-19 Clinics and Hospitals of Nepal - Bhattarai, S.; Neopane, A. K.; Shrestha, B.; Dangol, S. R.; Shrestha, S. K. D.; Dutta, A.; Adhikari, G.; Dahal, S. (Kathmandu University Medical Journal, 2022)
Background The coronavirus pandemic preparedness and response activities began in Nepal after the detection of the first case on 24 January 2020. Highest daily case record in June 2020 was 671, but it reached above 5,000 in October 2020. Objective This study assessed preparedness and response status of government designated COVID-19 clinics and various level hospitals. Method A web-based survey was conducted among government designated COVID-19 clinics and Level hospitals in June 2020. The Medical Operations Division of the COVID-19 Crisis Management Center (CCMC) retained contact list of focal person in each facility for regular updates. Forty-nine out of 125 clinics and all level hospitals (five Level-1, 12 Level-2, three Level-3) provided responses. Result There were 25 or less isolation beds in the majority of COVID-19 clinics (83.7%) and Level-1 hospitals (60%), whereas the majority of Level-2 (92%) and Level-3 hospitals (67%) had arranged >25 beds. Only five clinics, one Level-1 hospital, six Level-2 and two Level-3 hospitals had a surge capacity of additional 20 or more isolation beds. Only one-fourth of the designated health facilities had arranged separate isolation facility for vulnerable population. Majority of the designated clinics and Level-1 hospitals had five or less functional ICU beds and functional ventilators. Very few Level-2 hospitals had > 10 ICU beds and > 10 ventilators. Healthcare workers in the majority of facilities were trained on donning/doffing, hand washing, swab collection, and healthcare waste management, but, a very few received formal training on patient transport, dead body management, epidemic drill, and critical care. Conclusion This study revealed insufficient preparation in COVID-19 facilities during the initial phase of pandemic. The findings were utilized by the government stakeholders at central, provincial and local levels for scaling up surge capacity and improving health services at the time of case surge. As the pandemic itself is a dynamic process, periodic assessments are needed to gauze preparedness and response during different phases of disease outbreak.